Effects of lysolecithin supplementation in low-energy diets on growth performance, nutrient digestibility, viscosity and intestinal morphology of broilers. Issue 2 (4th March 2018) - Papadopoulos, G. A.; Poutahidis, T.; Chalvatzi, S.; Di Benedetto, M.; Hardas, A.; Tsiouris, V.; Georgopoulou, I.; Arsenos, G.; Fortomaris, P. D.
ABSTRACT: 1. The study aimed to investigate the effect of lysolecithin supplementation in low-energy diets on growth, nutrient digestibility and intestinal mucosa characteristics of broilers. 2. A total of 800 one-d-old Ross 308 broiler chickens were assigned to 4 dietary treatments consisting of 10 replicates of 20 broilers each. Broilers were fed with 4 different diets: (i) HE: positive control group broilers received a diet with unaltered energy; (ii) LE: negative control group broilers received a diet with lower energy of about 0.27 MJ/kg; (iii) LElys500: broilers received a diet similar to LE supplemented with 500 g/tn lysolecithin product (Lysoforte Booster Dry TM ); and (iv) LElys300: broilers received a diet similar to LE supplemented with 300 g/tn lysolecithin product. The experimental period was 42 d. 3. Body weight gain in treatments HE was higher than LE during the overall experimental period, while LElys500 and LElys300 had intermediate values. Feed conversion ratio was lower in HE and LElys500 than LE group, while the LElys300 had intermediate values. Fat digestibility was improved in both LElys 500 and LElys300 compared to the HE group. Apparent metabolisable energy (AMEn) was higher in HE, LElys500 and LElys300 than LE. Ileum viscosity at 42 d was also affected, being higher in LE group compared to HE. At 28 d mucosal thickness was lower both in LElys500 and LElys300 compared to HE and LE, while no difference occurred between treatment proliferation patterns of duodenal epithelial cells. 4. These findings indicated that lysolecithin supplementation at 500 g/tn of feed in low-energy diets maintained broiler performance. Supplementation of reformulated low-energy diets induced an increase in digesta viscosity. Lysolecithin supplementation resulted in variable alterations in the duodenum mucosal morphology.